Design, synthesis and cell imaging of a simple peptide-based probe for the selective detection of RNA. Issue 21 (15th February 2021) - Duan, Wenxiu; Huang, Fengyang; Bi, Yihui; Zhu, Lingling; Wang, Daojiong; Liu, Yi; Wu, Jiang; Ge, Yushu; Liu, Dan
Abstract : A novel peptide-based chemosensor P1 for detecting RNA both in vitro and in cells is reported. Successful RNA imaging in living cells has been performed. Abstract : Here we present a novel peptide-based fluorescent "turn-on" molecule P1 for detecting RNA, in a double or single strand, AU-rich or CG-rich. Both computational and experimental studies indicate that the detection efficiency depends on the binding affinity of P1 and conformational changes. P1 could be applied for cell imaging without any additional transfection vectors. Selective detection of RNA in cells was determined by RNase digestion. Successful application of P1 for RNA imaging in cell mitosis reveals that it may have broad applications in research, biotechnology and medical science.